Failure of noninvasive ventilation in adult patients with acute asthma exacerbation - Bahloul, Mabrouk; Chtara, Kamilia; Gargouri, Rahma; Majdoub, Ali; Chaari, Anis; Bouaziz, Mounir (Journal of Thoracic Disease, 2016)
We read with interest the article entitled “Use of noninvasive ventilation in adult patients with acute asthma exacerbation” by Ganesh et al. (1). The authors have concluded that non-invasive ventilation (NIV) can be used initially in patients with acute asthma exacerbation, as it was associated with shorter duration of hospital stay and can prevent the morbidity of mechanical intubation. In this regard I would like to make the following observations.